2015
DOI: 10.1007/s00167-015-3565-0
|View full text |Cite
|
Sign up to set email alerts
|

Does patellofemoral geometry in TKA affect patellar position in mid-flexion?

Abstract: Comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
(121 reference statements)
0
10
0
Order By: Relevance
“…The discrepancies between the native and prosthetic knees in terms of sulcus height (H) values, which are exemplified in Fig. 2, may be related to different positioning of the patella following TKA; as the position of the patella determines the lever arm of the extensor mechanism, such inappropriate design of the prosthetic components is likely to influence quadriceps efficiency as well as joint reaction forces and contact levels on the femoral trochlea or condyles [11]. Such differences might also cause the component to become anteriorly displaced, as evident in the higher sulcus height (H) values noted for the 0 and 90° cross-sections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The discrepancies between the native and prosthetic knees in terms of sulcus height (H) values, which are exemplified in Fig. 2, may be related to different positioning of the patella following TKA; as the position of the patella determines the lever arm of the extensor mechanism, such inappropriate design of the prosthetic components is likely to influence quadriceps efficiency as well as joint reaction forces and contact levels on the femoral trochlea or condyles [11]. Such differences might also cause the component to become anteriorly displaced, as evident in the higher sulcus height (H) values noted for the 0 and 90° cross-sections.…”
Section: Discussionmentioning
confidence: 99%
“…In the 0° cross-section, the PRF is relatively small, and thus the decrease in lateral tilt angle (α) has little effect on the PRF vector or the stability of the patella. However, recent studies revealed that quadriceps forces are highest between 70 and 110° [11, 20, 21]. In the 45° cross-section (67.5° of knee flexion), the PRF is relatively high, and thus the decrease in lateral tilt angle (α) might result in a decrease in the PRF vector and subsequent patellar instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While patellar morphology is often associated with excessive tilt, Wiberg type C being most predisposed (23,24), it does not necessarily correlate with patellar subluxation or osteosclerosis (22,25), and pressure distribution data cannot be extrapolated to conclude on AKP or clinical outcomes. Moreover, most studies of patellar congruence are either radiographic, and therefore represent limited static data with inconsistent reliability (26), or intra-operative with the joint capsule open and therefore under non-physiological conditions (27).…”
Section: Introductionmentioning
confidence: 99%